A Randomized, Double Blind, Placebo-Controlled Study On The Efficacy Of Bifidobacterium Longum BB536 In Reducing Symptoms Of Respiratory And Gastrointestinal Diseases Among Young Children - Lau, Amy Sie Yik (2018)
Probiotics have been extensively used and may be effective in alleviating symptoms and reducing the occurrences of gastrointestinal and respiratory diseases, but their efficacy remains controversial due to strain and host dependency. Children who are attending day care centres have 1.5 to 3.0 times higher risk of getting respiratory and gastrointestinal diseases than those who are not attending day care centres. This randomized, double-blind and placebo-controlled trial which was carried out for a period of 10 months was aimed to evaluate the effects of oral administration of Bifidobacterium longum BB536 in preventing acute diarrhea and/or respiratory-related diseases among young children in Malaysia.